Pulmonary nocardiosis: A Single Center Study. (2020) - Oliveira Cabrita, Bruno Miguel; Correia, Sílvia; Jordão, Sofia; Correia de Abreu, R.; Alves, Valquíria; Seabra, Bárbara; Ferreira, Jorge
Abstract: Objectives: Nocardiosis is a rare infection caused by Nocardia spp., a gram-positive bacteria non-commensal of the human flora. Nocardiosis usually presents with lung infection but may disseminate to other organs, most frequently the brain. The major risk factor is immunosuppression, but lung diseases also increase the risk of infection. Treatment with antibiotics is usually prolonged. In this study, we made a retrospective analysis of pulmonary nocardiosis cases and a review of the available literature. Methods: We made a retrospective analysis of all pulmonary nocardiosis cases from 13 years (January 2005 to December 2017) in our institution, selecting patients from pulmonology and infectious diseases consultation. Results: We found four patients diagnosed with pulmonary nocardiosis, three males (patients 1, 2 and 3) and one female (patient 4). Median age was 71 ± 15 years old. Different specimens were identified ( N. cyriacigeorgica, Nocardia spp., N. nova, and N. wallacei/transvalensis ). Bronchofibroscopy with bronchoalveolar lavage culture was the most frequent diagnostic procedure (patients 1 and 4). Only patient 2 presented an unfavorable response to treatment and died from septic shock. Conclusions: Pulmonary nocardiosis has a good prognosis if diagnosed early and treated adequately. It should always be considered in the differential diagnosis of pulmonary infections concomitant with brain or other soft tissue lesion, especially in immunocompromised patients.